Tinjauan Hukum Pidana Islam Terhadap Pemalsuan Label Halal Dalam Produk Makanan - Raihan Ryanta Akbar; Imam Yazid (Institut Agama Islam Negeri (IAIN) Bone, 2026)
This study aims to analyze the form and mode of the crime of falsifying halal labels on food products in Indonesia and to examine the effectiveness of Muslim consumer protection from the perspective of positive law and Islamic criminal law (jinayah). In addition, this study aims to find out how halal label falsification is seen in Islamic sharia norms and its position in the national legal system, especially related to the protection of Muslim consumers' rights to halal product information. The research method used is normative legal research (normative juridical) with a legislative approach, a case approach, and a legal sociology approach. The research data was obtained through library research which includes primary, secondary, and tertiary legal materials, such as laws and regulations, legal literature, ulama fatwas, the Qur'an, and Hadith. The data was analyzed using a descriptive qualitative analysis method by interpreting and comparing positive legal norms and Islamic criminal law related to halal label falsification. The results of the study show that the falsification of halal labels on food products is generally carried out through the inclusion of halal logos without an official certificate. In Islamic criminal law, this act is included in jarimah ta'zir because it contains elements of fraud and forgery. In positive law, the action violates the provisions of laws and regulations regarding halal product assurance and consumer protection.